Developing Mathematics Learning Activities Using Open Approach Together with Think-Pair-Share Technique to Promote the Ability to Solve Mathematical Problems in Grade 6 Students - Srisuk, Supakan; Thongkanluang, Sirisawas; Sangarwut, Anchalee (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this research were: 1) Develop mathematics learning activities using open Approach Together with Think-Pair-Share Technique to achieve an efficiency standard of 80/80 and an effectiveness index (E.I.) of at least 0.50, as per the established criteria. 2) Compare students' academic achievement before and after the implementation of the learning activities. 3) Compare students' mathematical problem-solving ability before and after the learning activities. 4) Examine students' satisfaction with mathematics learning activities using open Approach Together with Think-Pair-Share Technique. The sample group consisted of 35 Grade 6/5 students from Watprathumtayakaram School, selected through cluster sampling. The research instruments included: Lesson plans, An academic achievement test, A mathematical problem-solving ability test, A student satisfaction questionnaire. Data were analyzed using basic statistics, including percentage, mean, standard deviation, and t-test. The research findings revealed that: 1) The mathematics learning activities using open Approach Together with Think-Pair-Share Technique had an efficiency value of 79.67/78.22, meeting the predetermined criteria, and an effectiveness index (E.I.) of 0.56, aligning with the standard requirement. 2) Students' academic achievement after the learning activities was significantly higher than before at the .05 level. 3) Students' mathematical problem-solving ability after the learning activities was significantly higher than before at the .05 level. 4) Students' satisfaction with the learning activities was at a high level, with a mean score of 4.36. These findings concluded that the mathematics learning activities using open Approach Together with Think-Pair-Share Technique effectively enhances the mathematical problem-solving ability of sixth-grade students.